1998
DOI: 10.1037/0022-006x.66.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Defining empirically supported therapies.

Abstract: A scheme is proposed for determining when a psychological treatment for a specific problem or disorder may be considered to be established in efficacy or to be possibly efficacious. The importance of independent replication before a treatment is established in efficacy is emphasized, and a number of factors are elaborated that should be weighed in evaluating whether studies supporting a treatment's efficacy are sound. It is suggested that, in evaluating the benefits of a given treatment, the greatest weight sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
1,935
0
68

Year Published

2000
2000
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 2,428 publications
(2,052 citation statements)
references
References 55 publications
16
1,935
0
68
Order By: Relevance
“…In addition, only a few studies compared the intervention to both a waitlist control group and a timematched comparison condition. To evaluate the efficacy of behavioral interventions, trials should include both a rival treatment and no intervention control group [65]. Thus, future studies should utilize research designs that allow the effect of treatment intensity to be controlled for by using comparison treatments of equal length and intensity.…”
Section: Research Designs To Evaluate Intervention Efficacy Future Stmentioning
confidence: 99%
“…In addition, only a few studies compared the intervention to both a waitlist control group and a timematched comparison condition. To evaluate the efficacy of behavioral interventions, trials should include both a rival treatment and no intervention control group [65]. Thus, future studies should utilize research designs that allow the effect of treatment intensity to be controlled for by using comparison treatments of equal length and intensity.…”
Section: Research Designs To Evaluate Intervention Efficacy Future Stmentioning
confidence: 99%
“…Several studies have identified good short and long-term efficacy for FBBT (Epstein et al, 1985a(Epstein et al, , b, 1990a(Epstein et al, , b, 1995. However, evidence of generalization across settings is required for FBBT to be considered a 'well-established treatment' (Chambless and Hollon, 1998). British reviewers have concluded that there is a 'limited amount of quality data on childhood obesity programmes' (Summerbell et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Most tobacco users express a desire to achieve long-term abstinence from tobacco use and make numerous unsuccessful quit attempts over the course of many years (Borland, Partos, Yong, Cummings, & Hyland, 2012;CDC, 2011). Evidence-based treatments for tobacco use and dependence greatly improve the chances that quit attempts result in long-term abstinence (Chambless & Hollon, 1998;Compas, Haaga, Keefe, Leitenberg, & Williams, 1998;Fiore et al, 2008;Zwar et al, 2004). Increasing the availability of high-quality evidence-based treatment for tobacco use and dependence will make it more likely that tobacco users use evidence-based treatments and that quit attempts translate into long-term abstinence.…”
mentioning
confidence: 99%